Fresno-Merced Counties Legal Services Christmas Party at Patience Milrod's Home - Watkins, Howard::::::::: (1980)
Kathy Reilley reading her card; Robert Higgins, Scott Williams, David Cisneros, Joe Mendez, Faheem Hameed, Patience Milrod 3400 Block of E. Montecito Avenue